Rice panicle detection from unmanned aerial vehicle (UAV) imagery via image restoration and pseudo-depth prior - Pan Pan; Haochun Li; MingXia Li; Saiyang Xu; Zhihao Guo; Guoping Yu; Long Yi; Maomao Li; Guomin Zhou; Jianhua Zhang (Computers and Electronics in Agriculture, 2026)

Mitigation of antibiotic resistance risk in aerobic sludge by zero-valent iron: From pathogen reduction to conjugation inhibition and network weakening - Ying Wu; Lin Zhu; Guoping Lin; Xuezhu Han; Jingpeng Li; Jiaming Yi; Dan Huang; Meizhen Wang (Bioresource Technology, 2026)

Identification of HsfA9 and a network of regulators involved in resistance to bacterial wilt under high temperature in tomato - Jing Li; Wenhao Zhong; Qiaoping Mo; Xiaoyu Qi; Juan Li; Hongling Yang; Jianghua Cai; Mengyun Xu; Guoping Wang (Plant Science, 2026)

IMI targets abnormal lipid metabolism by inhibiting intestinal TAS2Rs - Jiafan Liang; Yixuan Li; Wentao Xu; Guoping Zhao; Yanbo Wang (Food Chemistry, 2026)

Topology-engineered hydrogel with cellulose nanosheets for robust and high-capacity zinc-ion batteries - Wenxuan Lei; Heng Huang; Wenyu Liu; Lingfeng Zhou; Guoping Li; Pan Chen; Zu Chang; Jiangfeng Qian; Ang Lu (Carbohydrate Polymers, 2026)

CEN-Display: Construction and optimization of a surface display system in Saccharomyces cerevisiae CEN.PK2-1C - Zhengzheng Li; Bei Zhang; Meizi Liu; Chenxi Deng; Xinyu Wu; Lixian Wang; Kevin J. Verstrepen; Guoping Zhao; Yanfei Zhang (Bioresource Technology, 2026)

Human sweet, umami and bitter taste receptors: From decoders of taste perception to sentinels of systemic metabolism and health - Yuxiang Gu; Yixuan Cui; Kangli Guo; Guoping Zhao; Xing Li; Weixi Yang; Yanbo Wang (Trends in Food Science & Technology, 2026)

Global peatlands formed via paludification since the Last Glacial Maximum are more conducive to absorbing CO2 - Yunlong Gao; Jiangtao Gao; Jinxin Cong; Dongxue Han; Guangxin Li; Guoping Wang; Bei Li; Chuanyu Gao (Global and Planetary Change, 2026)

Effects of Lactiplantibacillus plantarum fermentation on the flavor profile and in vitro digestive characteristics of easy-to-swallow surimi gels - Fei Wang; Xinyu Liu; Yao Wang; Jinping Zhang; Xiaoling Lu; Xiang Li; Xugan Wu; Guoping Zhao; Jing Xie; Xichang Wang; Weiqiang Qiu (Food Chemistry, 2026)

Synergistic mechanisms of gravity waves and windward slopes in intensifying regional rainstorms: A Sichuan Basin case study - Yizhou Xu; Guoping Li; Xiaoyu Zhang; Yuanchang Dong; Kejun Wang (Atmospheric Research, 2026)

A decision-support framework for balancing growth, profit and environmental impacts in aquaculture feeding - Chunlin Chen; Youbang Guan; Lihua Song; Guoping Lian; Daoliang Li; Ran Zhao; Lian X. Liu; Michael Short (Aquacultural Engineering, 2026)

Reliability-aware query restoration for embedded real-time object detection in degraded underwater vision systems - Bo Liu; Xiaoqun Liu; Yongqiang Gu; Guoping Wang; Aihua Zhang; Zhaoye Xing; Shengdong Li (Frontiers in Marine Science, 2026)
Embedded underwater vision systems require real-time object detection that remains reliable in the face of turbidity, color attenuation, low contrast, weak boundaries, and cluttered backgrounds. In real-time detection transformer (RT-DETR)-style detectors, these degradations affect the ranking and selection of encoder candidates used to initialize decoder queries. This study proposes a degradation-aware query reliability restoration framework for RT-DETR, termed DQR-RTDETR. The Candidate Reliability Prior (CRP) estimates candidate trustworthiness from encoder memory, Stability-Preserving Query Reliability Recalibration (QRR) adjusts top- K candidate scores and selected-query features, and Scale-Aware Local Evidence Compensation (SLEC) preserves local cues for small or weakly structured targets. On the SeaClear Marine Debris Detection and Segmentation Dataset (SeaClear), averaged across three random seeds, DQR-RTDETR improves mean average precision across intersection-over-union thresholds from 0.50 to 0.95 (mAP@0.5:0.95) from 0.6998 ± 0.0029 to 0.7444 ± 0.0026 and average precision at an intersection-over-union threshold of 0.75 (AP75) from 0.8030 ± 0.0038 to 0.8615 ± 0.0044, while adding only 0.05 million parameters. Validation on the TrashCan underwater marine-debris dataset and the Detecting Underwater Objects dataset (DUO), degradation-grouped SeaClear analysis, and query-level diagnostics show consistent gains in accuracy, strict localization, and selected-query quality. Deployment on an NVIDIA Jetson Orin NX using Robot Operating System 2 (ROS 2) and TensorRT achieves 18.7 frames per second (FPS) with a mean end-to-end latency of 52.8 milliseconds. These results indicate that restoring query reliability is an effective, compact intervention for edge-deployable underwater electronic vision systems.

Influence of gravity waves excited by multiscale topography on mesoscale convective systems and rainstorms: A Sichuan Basin case study - Yizhou Xu; Guoping Li; Yuanchang Dong; Xiaoyu Zhang; Mengjia Chen (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

The role of heavy reflux in pressure swing adsorption for industrial carbon capture - Jinbiao Luo; Hao Yuan; Yalou Guo; Shuangjun Li; Qingchuan Chen; Tao Qi; Guoping Hu (Chemical Engineering Journal, 2026)

Evolution and functional characterization of the MdSKP8 gene as a conserved hub integrating hormone and antioxidant pathways for salt tolerance in apple - Miao Shao; Yongqing Feng; Shixiong Lu; Shangwen Yang; Jian Li; Xinyu Li; Zonghuan Ma; Guoping Liang; Baihong Chen; Juan Mao (Plant Cell Reports, 2026)

Fracture Development, Mechanisms, and Effectiveness in Tight Sandstone Reservoirs: Case Study of the Xujiahe Formation, Northeastern Sichuan Basin - Zhuoyi Li; Guoping Liu; Kewei Zu; Xing Zhang; Yunlong Xu; Chengxiang Wan; Jiasi Li; Xiaofei Zhao; Yuzhe Wang; Haoyu Wang; Tao Hu (Journal of Earth Science, 2026)

Synergistic Effects of Maize Volatiles on Pheromone Trap Captures of the Fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) - Fida Hussain Magsi; Amees Ullah; Yihui Ma; Guoping Li; Jianrong Huang; Muhammad Sohaib; Songke Li; Xincheng Zhao; Hongqiang Feng (Journal of Chemical Ecology, 2026)

Identification of KL29 type acinetobacter baumannii phage of obolenskvirus subfamily and tail-associated depolymerase activity - Jinpan Wei; Tao Yu; Qiang Wang; Can Wang; Xuefeng Li; Guoping Lu; Lijuan Li; Aihui Xu; Lei Zhao (Archives of Virology, 2026)

PBAT/TPS-based intelligent films loaded with anthocyanin microcapsules for monitoring shrimp freshness - Zhaocan Li; ShuYi Zhou; Yujuan Jin; Yanbo Wang; Huafeng Tian; Guoping Li (Innovative Food Science & Emerging Technologies, 2026)

Thiosulfate-Driven redox buffering enables efficient nitrogen removal and norfloxacin degradation in mixed denitrifying systems - Jin Qian; Xinqi Li; Xiangning Xu; Dandan Zhang; Guoping Xiang; Zichen Wang; Zhen Zhang; Mengxue Liu; Wen Hao; Di Wu (Bioresource Technology, 2026)

Efficient EVA decapsulation using ethyl lactate for delaminating and recycling of end-of-life crystalline silicon photovoltaic modules - Shangming Wang; Yunan Chen; Qiuyu Fang; Xiaofeng Li; Qiang Wang; Guoping Zhang; Yi Zhang; Bin Chen (Waste Management, 2026)

Microbial energy from ambient physical fields - Shungui Zhou; Guoping Ren; Bing Li; Yong Yuan; Jiangtao Gao; Christopher Rensing (Science Bulletin, 2026)

Pollen-based response patterns of vegetation dynamics to environmental changes during the early-mid Holocene in the Ningshao Plain, China - Zhen Li; Chunmei Ma; Zijing She; Haiyan Li; Konglan Shao; Bin Zhou; Zhujun Hu; Qing Yang; Guoping Sun; Michael Meadows; Hongbo Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Heavy-metal and nutrient enrichment triggered a regime shift in marsh diatom assemblages over the past millennium - Dongxue Han; Jinxin Cong; Lin Li; Guoping Wang; Chuanyu Gao (Journal of Environmental Management, 2026)

Crafting cellulose hollow microspheres with cellulose nanosheets - Wenxuan Lei; Heng Huang; Ruobing Liang; Guoping Li; Pan Chen; Jiechun Xiang; Ang Lu (Carbohydrate Polymers, 2026)

Modeling ammonia nitrogen dynamics coupled with fish growth physiology in recirculating aquaculture systems - Lihua Song; Yingyi Chen; Daoliang Li; Chunlin Chen; Liang Wang; Tao Chen; Guoping Lian (Aquacultural Engineering, 2026)

Food-grade abalone muscle hydrolysates as affected by high-pressure homogenization: An in-depth investigation into air-water interfacial behavior of their proteins - Jinzhen Li; Wanyi Wu; Wenhong Cao; Haisheng Lin; Jialong Gao; Mingtang Tan; Zhongqin Chen; Guoping Zhu; Huina Zheng (Food Chemistry, 2026)

Uncovering the role of Li+-H2O ion-dipole interaction in zeolite deactivation - Chenghao Liu; Yong Li; Zhe Lu; Shuzhuang Sun; Yong Wang; Zhifu Liu; Gang (Kevin) Li; Jingyue Shang; Songbai Hu; Lunhua He; Tao Qi; Guoping Hu (Chemical Engineering Journal, 2026)

Influence mechanism of eastward-moving mesoscale gravity waves on Southwest vortex and its precipitation - Yizhou Xu; Guoping Li; Xin Xie; Yuanchang Dong; Mengjia Chen (Meteorology and Atmospheric Physics, 2026)

Decolorization of Antarctic krill hydrolysate for salt reduction in surimi gel: improvement of taste, gel properties, and flavor profile - Yurui Zhang; Bo Wang; Yan Li; Xin Jiang; Shangkun Li; Keqiang Lai; Guoping Zhu; Wenzheng Shi (Food Research International, 2026)

Phyllosphere microbiome-physicochemical dynamics shape nitrogen resorption efficiency divergence during leaf senescence in subtropical forests of southern China - Bing Xue; Guoping Tang; Zhongkai Ren; Linwei Zeng; Xiaobin Li; Yuqi Li; Nan Jiang (Forest Ecology and Management, 2026)

Role of mitochondrial biogenesis in methanol-induced neurobehavioral changes in rats - Guoping Li; Xiaohong Du; Xinqiao Wang; Xiaojie Han; Mengnan Peng; Chen Nan (Toxicology Letters, 2026)

Bioengineering extracellular vesicles for enhanced therapeutic functionality and clinical potential in the cardiovascular system - Yongtao Wang; Meiyu Hu; Michail Spanos; Shihui Xu; Jiaxin Song; Guoping Li; Dragos Cretoiu; Junjie Xiao (Science Bulletin, 2026)

A 500-year cycle of demographic expansion and contraction in the lower Yangtze and adjacent coastal region during the Holocene driven by East Asian summer monsoon oscillations - Deke Xu; Yuhai Wang; Keyang He; Hao Li; Yajie Dong; Jun Kuang; Zhigang Zhang; Bing Song; Yulong Niu; Guoping Sun; Yonglei Wang; Jiatong Lu; et al. (Quaternary Science Reviews, 2026)

Integrated metabolomics and transcriptomics analyses reveal the molecular mechanism of anthocyanin accumulation in veins and leaves of Broussonetia papyrifera under cold stress - Xiangxue Yu; Rui Ni; Dingguo Zhang; Bo Chen; Qian Li; Ziyu Yang; Chenjing Li; Fuyuan Liu; Yongtao Xia; Guoqing Hou; Guoping Wang; Pengzhi Mao; et al. (Plant Science, 2026)

Magnetic extraction of highly polar pesticides: Method optimization and mechanism - Zhuangzhuang Shi; Huiling Shi; Ning An; Jinwang Li; Guoping Zhao; Xiaoxu Zhang; Xuefeng Yin (Food Chemistry, 2026)

Regionally modulated radiomics analysis in PET/CT imaging: application to prognosis prediction of head and neck cancer - Yuan Sheng; Guoping Shan; Xue Bai; Binbing Wang; Yue Feng; Chong Xu; Yihao Li; Guoping Zuo; Hui Xu (Physical and Engineering Sciences in Medicine, 2026)

Daily-scale spatiotemporal prediction of thin sea ice thickness during the early freezing season based on EOF-Trans - Jikun Liu; Guoping Zhang; Shuai Xing; Ming Gao; Pengcheng Li; Dandi Wang; Bo Zheng (Frontiers in Marine Science, 2026)
The accelerated decline of Arctic sea ice is profoundly reshaping regional climate regimes. Sea ice thickness (SIT), particularly under thin-ice conditions, is an important indicator for assessing early-season Arctic sea ice variability, and accurate prediction of its spatiotemporal evolution during the early freezing period is essential for characterizing short-term sea ice changes. In recent years, deep learning has emerged as a complementary approach to traditional sea ice prediction methods. However, existing deep learning-based studies have not fully exploited the large-scale spatial patterns and temporal contextual dependencies inherent in satellite-derived sea ice thickness. To address this limitation, this study proposes a spatiotemporal prediction framework named EOF-Trans for predicting daily-scale variability of thin sea ice thickness during the early freezing season. The method employs Empirical Orthogonal Functions (EOF) to decompose the sea ice thickness field into temporal mode series, utilizes a Transformer architecture to learn the temporal evolution characteristics, and subsequently reconstructs the predicted outputs back into the spatial thickness field by EOF, thereby enabling spatiotemporal sea ice prediction up to a leadtime of 21 days. Experimental results in the Beaufort Sea indicate that the proposed EOF-Trans framework significantly outperforms numerical models and classical deep learning architectures such as U-Net and ConvLSTM. On the 2022–2023 test set, it achieves a correlation coefficient of 88.04%, representing a 2% improvement over U-Net. Even at a leadtime of 21 days, the correlation remains approximately 84%, with the maximum spatial bias not exceeding 0.5 m. These results indicate that EOF-Trans effectively captures spatiotemporal regularities present in thin sea ice thickness, providing a complementary data-driven perspective for short-term sea ice prediction during the early freezing season.

Numerical investigation of critical cavitation to flow around rough flexible hydrofoil - Yibing Hou; Bin He; Shutian Li; Huaqing Zhou; Kai Xie; Guoping Wang; Pingxin Wang (Ocean Engineering, 2026)

Carbon balance in an agriculture-disturbed forested headwater stream in South China: Variations and environmental controls - Houbing Chen; Yangbo Yu; Xupeng Fang; Nan Jiang; Bing Xue; Yuqi Li; Guoping Tang (Journal of Environmental Management, 2026)

Excellent infrared radiation performance and significant energy-saving efficiency of LaAlO3 ceramics via Ca2+/Co2+ co-doping - Qinghu Wang; Yangxi Liu; Guoping Wei; Liang Huang; Xueqing Wang; Shaobai Sang; Yibiao Xu; Xiong Liang; Yawei Li; Jiangtao Li; Olena Volkova; Emad M.M. Ewais; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Activation of Alcohol Acetyltransferases by multiple transcription factors of Docynia delavayi regulates volatile ester biosynthesis” [Food Bioscience 75 (2026) 108027] - Guoping Liu; Yingjie Zhou; Lirui Wang; Siguang Li; Dawei Wang (Food Bioscience, 2026)

Activation of Alcohol Acetyltransferases by multiple transcription factors of Docynia delavayi regulates volatile ester biosynthesis - Guoping Liu; Yingjie Zhou; Lirui Wang; Siguang Li; Dawei Wang (Food Bioscience, 2026)

Role of the AMPK/PGC-1α/SIRT3-Mediated Mitochondrial Dysfunction in the Neurotoxicity of Methanol - Xiaojie Han; Mengnan Peng; Xinqiao Wang; Yundi Hu; Guoping Li; Yanan Song; Yanling Lv; Nan Chen (Molecular Neurobiology, 2026)

Analysis and rapid prediction of underwater vehicle hydrodynamic loads during water-exit integrating CFD with GA-LSTM - Shutian Li; Guoping Wang; Bin He; Genyang Wu; Yibing Hou; Yu Feng; Jinxin Tang (Ocean Engineering, 2025)

Permafrost peatland development at thermokarst lake margins in the northern Greater Khingan Mountains of Northeast China: Rapid areal increase and carbon accumulation since the 1950s - Jiangtao Gao; Jinxin Cong; Guangxin Li; Yingjie Shi; Dongxue Han; Guoping Wang; Chuanyu Gao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Volatile markers as indicators of salmon freshness states identified via volatolomics and machine learning - Qian Hu; Bingwu Zhou; Guoping Li; Ranran Xing; Ying Chen; Jiukai Zhang (Food Research International, 2025)

Unraveling cross-variations in fruit aroma and color during ‘Red Delicious’ bud sport: Insights from targeted metabolomics and transcriptomics - Miao Shao; Yongqing Feng; Shangwen Yang; Huimin Gou; Xin Li; Zonghuan Ma; Guoping Liang; Baihong Chen; Juan Mao (Food Chemistry, 2025)

Design and synthesis of novel diamines for ultra low-temperature curable polyimides with enhanced copper adhesion - Jialin Tian; Xialei Lv; Wentao Wang; Jinhui Li; Jialin Zhang; Jie Liu; Chao Zhao; Guoping Zhang; Rong Sun (Chemical Engineering Journal, 2025)

Cool/drought triggered rapid expansion of floating peat mat in shallow lake as new hotspot of carbon sink - Jinxin Cong; Shengzhen Ji; Guangxin Li; Chao Gong; Dongxue Han; Guoping Wang; Chuanyu Gao (CATENA, 2025)

Heterologous expression of nodulation signaling pathway genes enhances grain yield in rice - Zheng Li; Hao Li; Guoping Tang; Jiashan Wu; Zhongming Zhang; Renliang Huang; Yangrong Cao (Plant Molecular Biology, 2025)

Soil and enzymatic C:N:P stoichiometry response to carbon and nutrient input: evidence from long-term fertilization experiments - Qiong Xiao; Yaping Huang; Guoping Chen; Kailou Liu; Yu Jiang; Boku Zhou; Ping Zhu; Xiaori Han; Junyong Ma; Shutang Liu; Shaomin Huang; Aijun Zhang; et al. (Plant and Soil, 2025)

Urban trash bins as reservoirs of multidrug-resistant Enterococcus with shared resistance genes across clinical and environmental niches - Jie Li; Xiaorui Mao; Yu Song; Xiaohe Hu; Guoping Zhao; Biao Tang (Journal of Hazardous Materials, 2025)

Predictive biomarkers for valproic acid-induced hepatotoxicity in Chinese patients with epilepsy: the role of metabolites and genetic polymorphisms - Dingsheng Wen; Zhuojia Chen; Ziyi Chen; Xue Bai; Hongliang Li; Juan Chen; Qiling Dai; Guoping Zhong; Jiaming Qin; Guanzhong Ni; Min Huang; Liemin Zhou; et al. (Food and Chemical Toxicology, 2025)

Dynamically programmable plant-derived scaffold coordinates alveolar bone repair cascade: Phase-adaptive integration from hemostasis to bone remodeling - Yeke Chen; Yumei Ning; Fang Dai; Yuting Yang; Chenjiang He; Kaiqiang Yang; Yichen Hu; Guoping Cheng; Li Song (Chemical Engineering Journal, 2025)

Exploring the trade-offs and synergies among ecosystem services to support ecological management in the Yangtze River Delta Urban Agglomeration - Song Yao; Yonghua Li; Xiangyang Quan; Guoping Huang; Jiren Xu (Journal of Environmental Management, 2025)

Historical effects of organic matter sources and fire intensity on permafrost peatland carbon dynamic in northern Great Khingan Mountains (China) over the last millennium - Jinxin Cong; Guangxin Li; Dongxue Han; Guoping Wang; Chuanyu Gao (Global and Planetary Change, 2025)

A 5-year field study to assess interannual variability and determinants of cotton fiber quality in intercropping systems - Haoyue Qin; Yurui Tang; Xin Li; Yurong Qiu; Jian Wang; Yingchun Han; Guoping Wang; Shiwu Xiong; Minghua Xin; Wenli Du; Lu Feng; Yongjiang Zhang; et al. (European Journal of Agronomy, 2025)

Co-transport behavior of aged polymeric methyl methacrylate nanoplastics and florfenicol antibiotic in porous media: Effects of electrolyte, pH, and aging duration - Lihui Tan; Ming Wu; Yanru Hao; Hui Li; Cehui Mo; Guoping Lu (Water Research, 2025)

Glycine intervention can alleviate imidacloprid-induced spermatogenic damage in rats - Zhihui Zhang; Weilong Cheng; Junsong Xiao; Yixuan Li; Guoping Zhao; Yanbo Wang (Reproductive Toxicology, 2025)

Fine particulate matter exacerbates asthma by activating STC2-mediated mitophagy through METTL3/YTHDF2-dependent m6A methylation - Yao Liu; Guoping Li; Anying Xiong; Jiliu Liu; Ruitong Zeng; Lei Zhang; Junyi Wang; Manling Jiang; Jie Gao; Ying Xiong; Xiang He (Journal of Hazardous Materials, 2025)

Evaluation of the degree of blending between virgin and aged asphalt in rejuvenated asphalt mixture based on multilayer inclusion theory - Jinguo Ge; Huanan Yu; Guoping Qian; Taojun Li; Yixiong Zhong; Ruochen Lei; Liang Zhou; Yuetan Ma; Tengfei Nian (Journal of Cleaner Production, 2025)

Unlocking the bioremediation potential of adapted Desulfovibrio desulfuricans in acidic low-temperature U-contaminated groundwater - Lei Zhou; Nan Bai; Rui Xiao; Zhendong Yang; Guoping Jiang; Huaqun Yin; Yujie Wang; Liangzhi Li; Delong Meng; Zhenghua Liu (Journal of Environmental Sciences, 2025)

Hydrochemical characteristics of carbonated waters and non-carbonated thermal waters of the Heyuan Deep Fault Zone in Guangdong, Southern China - Xianxing Huang; Linjun Xie; Yan Li; Guoping Lu (Geothermics, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

Enhanced deep denitrification for high-salinity wastewater treatment by constructing biofilm-based technology - Kun Ding; Shan Yang; Hao Hu; Zhenghao Li; Haoran Duan; Xiaoqiang Chen; Yankun Liu; Guoping Sheng (Journal of Environmental Management, 2025)

Customized screening of ACE2 regulatory peptides from oyster to mitigate LPS-induced acute lung injury based on SPR technology - Xiaoyu Xia; Caixing Wen; Wenhong Cao; Xiaoming Qin; Yujin Li; Haisheng Lin; Zhongqin Chen; Huina Zheng; Guoping Zhu; Jialong Gao (Food Bioscience, 2025)

Formation mechanism of overshooting convection in the southwest vortex circulation under the influence of mesoscale gravity wave - Yizhou Xu; Guoping Li; Xiaoyu Zhang; Yuanchang Dong; Xin Xie (Dynamics of Atmospheres and Oceans, 2025)

Debris-flow susceptibility assessment using deep learning algorithms with GeoDetector for factor optimization - Kun Li; Junsan Zhao; Guoping Chen; Yongping Li (Bulletin of Engineering Geology and the Environment, 2025)

Effects of carbon sources on nitrite removal and microbial diversity in mariculture water - Zhen Ding; Meiling An; Hongli Xu; Zhongping Xu; Ning Fu; Lushan Wang; Li Zhang; Guoping Li (Biologia, 2025)

Innovative dry magnetic separation for Enhanced recovery of magnetic iron oxides from coal fly ash - Zeyu Zhang; Qijing Zhu; Guangfa Huang; Yaoji Chen; Jun Li; Guoping Zhao; Xiaoling Peng; Jing Li; Xinqing Wang (Fuel, 2025)

The defect engineering design of COCN/L-CdS/Ni2P for promoting hydrogen energy generation from seawater coupling with photoreforming of plastics - Zhe Yin; Ziwen Wang; Jun Wang; Binglin Tang; Guoping Yu; Qiuyu Wang; Huanyu Chen; Kangzheng Li; Zhichao Zhang; Qingcheng Luo; Fuqin Zhang; Bo Lv (Fuel, 2025)

Integrated proteomics and metabolomics to clarify the essential beneficial mechanisms of L-theanine in alleviating ISO-induced cardiac damage in mice - Guoping Wang; Luwen Zhang; Wei Li; Xingxing Liu; Jichang Huang (Food Research International, 2025)

In-situ hybrid armor layer enabled by additive-anion synergy for dendrite-free and stable Zn anode - Yu Han; Yufei Xue; Teng Wang; Chiyu Zhang; Fuping Pan; Taotao Ai; Wenhu Li; Wei Ai; Guoping Gao; Kai-Jie Chen (Chemical Engineering Journal, 2025)

Low-severity fire promote carbon emissions in permafrost peatlands of the Great Khingan Mountains, Northeast China - Guangxin Li; Long Sun; Shengzhen Ji; Xiao Li; Jinxin Cong; Dongxue Han; Guoping Wang; Chuanyu Gao (CATENA, 2025)

Trans-scale Evaluation of Strengthening of a Shale by Injecting Oil- and Water-Based Nanoparticle Suspensions - Yongkang Wu; Yucheng Li; Shengmin Luo; Meng Lu; Nancy Zhou; Yuanzhi Qu; Yuan Geng; Guoping Zhang (Rock Mechanics and Rock Engineering, 2025)

Non-noble CeO2/CdS/NiS heterojunction for photoredox-catalyzed plastic waste selective synthesis and hydrogen production from natural seawater - Ziwen Wang; Qiuyu Wang; Zhe Yin; Man Zhang; Guoping Yu; Qingcheng Luo; Huanyu Chen; Binglin Tang; Kangzheng Li; Zhichao Zhang; Bo Lv (Fuel, 2025)

High instantaneous response quartz crystal microbalance humidity sensor for respiratory droplet detection - Jiaqi Lu; Xiangdong Chen; Xing Ding; Zhuolin Jia; Mengxi Zhang; Xiang Yu; Kun Tang; Fang Liu; Hui Li; Guoping Li (Chemical Engineering Journal, 2025)

Novel multi-lanthanide-substituted poly(polyoxometalate) nanocluster as electrode modified material used for the detection of persistent pollutant 2,4-dichlorophenol - Baoxing Zeng; Guoping Liu; Mengjia Zhou; Zhimin Zhang; Yanzhou Li; Lijuan Chen; Junwei Zhao (Chemical Engineering Journal, 2025)

Characteristics, interannual variation, and influence mechanisms of a double-halocline in the western Arctic Ocean during 2002 to 2022 - Yu Zhang; Tao Li; Guoping Gao; Hongxin Zhang; Yubin Yao; Xingyuan Zhu; Yongjun Wang (Acta Oceanologica Sinica, 2025)

Recent advances in taste transduction mechanism, analysis methods and strategies employed to improve the taste of taste peptides - Chunyong Song; Zhijun Wang; Hanqi Li; Wenhong Cao; Zhongqin Chen; Huina Zheng; Jialong Gao; Haisheng Lin; Guoping Zhu (Critical Reviews in Food Science and Nutrition, 2025)

Construction of low-toxicity cadmium sulfide/nitrogen-doped muti-walled carbon nanotubes for peroxymonosulfate activation: The crucial role of electron transfer - Jin Qian; Sai Bai; Mengqi Geng; Dandan Zhang; Guoping Xiang; Yichu Zhang; Yangju Li; Dongdong Chu; Di Wu; Rui Ma; Yueping Bao; Xiangning Xu; et al. (Environmental Research, 2025)

A strategy for addressing large-scale hinge issues in large two-dimensional planar phased array antennas - Li Pei; Liu Xiang; Cai Guoping; Liu Fucheng; Sun Jun; Zhu Dongfang (Advances in Space Research, 2025)

Microbial mechanisms of sulfate reduction for low-temperature bioremediation of acid-mined uranium sandstone groundwater - Rui Xiao; Zhenghua Liu; Min Xu; Guoping Jiang; Yang Peng; Cunzeng Li; Jie Wang; Huaqun Yin; Lechang Xu (Journal of Water Process Engineering, 2025)

Hysteresis of unfrozen water content of tailing mud with freeze-thaw and its correlation with electrical conductivity - Wanying Xu; Fangtao She; Weibin Zeng; Songhe Wang; Jiulong Ding; Xiaoliang Yao; Guoping Liu; Lei Li (Cold Regions Science and Technology, 2025)

Peanut–cotton intercropping to enhance soil ecosystem multifunctionality: Roles of microbial keystone taxa, assembly processes, and C-cycling profiles - Shijie Zhang; Yingchun Han; Guoping Wang; Lu Feng; Yaping Lei; Shiwu Xiong; Beifang Yang; Xiaoyu Zhi; Minghua Xin; Yahui Jiao; Xiao-Fei Li; Yabing Li; et al. (Agriculture, Ecosystems & Environment, 2025)

Pharmacokinetic-pharmacodynamic Modelling of NH600001 in Healthy Subjects and Patients Undergoing Gastroscopy - Yaxin Liu; Yun Kuang; Jie Huang; Dan Jiang; Yajie Cao; Qi Gao; Zifeng Li; Wen Ouyang; Saiying Wang; Qi Pei; Guoping Yang (The AAPS Journal, 2024)

Impact of metals exposure on lung function and serum club cell secretory protein among schoolchildren: A mixture and mediation analysis - Jie Li; Meili Shen; Ting Wang; Xiao Zhang; Wen Gu; Mengmeng Xu; Tongjin Yang; Jie Cui; Xin Xia; Guoping Chen; Siyu Zheng; Haoying Yang; et al. (Journal of Hazardous Materials, 2024)

Enhancing investment strategies for CCUS deployment in China: implications from a real options-based multiphase unequal investment approach - Yuan Chang; Siqi Gao; Ying Wei; Guoping Li (Environment, Development and Sustainability, 2024)

Fe-mordenite for high-performance N2 rejection - Zhi Yu; Jianing Yang; Seyed Hesam Mousavi; Penny Xiao; Xue Yan; Ali Zavabeti; Yongqiang Wang; Kaifei Chen; Zhe Jefferson Liu; Guoping Hu; Xiaoling Liu; Yu Zhou; et al. (Chemical Engineering Journal, 2024)

Unordered vacancies provide rapid migration pathways for sodium ion insertion/extraction in copper-deficient ternary Cu4Bi4Se9 - Xu Han; Guoping Liu; Weiqiang Kong; Luzheng Zhao; Wenruo Li; Farva Ilyas; Haoyuan Zhu; Jiancong Guo; Zhongsheng Wen (Chemical Engineering Journal, 2024)

Early-mid Holocene vegetation and diversity evolution on the Ningshao Plain, eastern China - Zhen Li; Chunmei Ma; Yufan Ni; Zeyu Liu; Bingling Wang; Zhujun Hu; Guoping Sun; Yonglei Wang; Michael Meadows; Hongbo Zheng (CATENA, 2024)

Genome-wide identification of Aux/IAA gene family members in grape and functional analysis of VaIAA3 in response to cold stress - Shixiong Lu; Min Li; Yongjuan Cheng; Huimin Gou; Lili Che; Guoping Liang; Juan Mao (Plant Cell Reports, 2024)

Efficient removal of phosphate and fluoride from phosphogypsum leachate by lanthanum-modified zeolite: Synchronous adsorption behavior and mechanism - Mengxuan Zhao; Xiaomeng Zhou; Junfeng Li; Fei Li; Xiaodi Li; Junxia Yu; Li Guo; Guoping Song; Chunqiao Xiao; Fang Zhou; Ruan Chi; Guoqing Feng (Journal of Environmental Chemical Engineering, 2024)

Impact of diatomit on the transport behavior of unmodified and carboxyl-modified nanoplastics in saturated porous media - Yuheng Wu; Ming Wu; Zhou Cheng; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu; Guoping Lu (Environmental Pollution, 2024)

Halogen-functionalized covalent organic frameworks for photocatalytic Cr(VI) reduction under visible light - Dong Cao; Jian Guan; Jingcheng Du; Qian Sun; Ji Ma; Jingguo Li; Jiangtao Liu; Guoping Sheng (Journal of Hazardous Materials, 2024)

Highly efficient recovery of phosphate and fluoride from phosphogypsum leachate: Selective precipitation and adsorption - Mengxuan Zhao; Xiaodi Li; Jun-xia Yu; Fei Li; Li Guo; Guoping Song; Chunqiao Xiao; Fang Zhou; Ruan Chi; Guoqing Feng (Journal of Environmental Management, 2024)

Residue changes, degradation, processing factors and their relation between physicochemical properties of pesticides in peanuts during multiproduct processing - Kai Cui; Jian Wang; Shuai Guan; Jingyun Liang; Liping Fang; Ruiyan Ding; Teng Li; Zhan Dong; Guoping Ma; Xiaohu Wu; Yongquan Zheng (Food Chemistry, 2024)

Response of bacterial ecological and functional properties to anthropogenic interventions during maturation of mine sand soil - Min Zhang; Xi Yu; Guoping Jiang; Lei Zhou; Zhenghua Liu; Xing Li; Teng Zhang; Jing Wen; Ling Xia; Xueduan Liu; Huaqun Yin; Delong Meng (Science of The Total Environment, 2024)

Co-composting of dewatered sludge and wheat straw with newly isolated Xenophilus azovorans: Carbon dynamics, humification, and driving pathways - Xuan Wu; Runyu Gao; Xiaorui Tian; Jiawei Hou; Yang Wang; Quan Wang; Daniel Kuok Ho Tang; Yiqing Yao; Xiu Zhang; Bowen Wang; Guoping Yang; Hua Li; et al. (Journal of Environmental Management, 2024)

AcrAB-TolC efflux pump overexpression and tet(A) gene mutation increase tigecycline resistance in Klebsiella pneumoniae - Zhaoxin Xia; Jing zhou; Nana Gao; Ge Li; Runde Liu; Guoping Lu; Jilu Shen (World Journal of Microbiology and Biotechnology, 2024)

Estimation of groundwater-level changes based on GRACE satellite and GLDAS assimilation data in the Songnen Plain, China - Jinliang Zhang; Zhong Lu; Chaoqun Li; Guoping Lei; Ziyang Yu; Kuo Li (Hydrogeology Journal, 2024)

Correction to: Estimation of evapotranspiration through an improved daily global solar radiation in SEBAL model: a case study of the middle Heihe River Basin - Jingqiu Yin; Xinfa Qiu; Shoubo Li; Guoping Shi; Huiyu Liu; Haixuan Zhou; Hanwei Wu (Theoretical and Applied Climatology, 2024)

Significance of non-DLVO interactions on the co-transport of levofloxacin and titanium dioxide nanoparticles in porous media - Yiqun Cui; Ming Wu; Guoping Lu; Zhou Cheng; Meng Chen; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Environmental Pollution, 2024)

Evolution and roles of mesoscale convective system during the Nocturnal Rainfall in Sichuan Basin and its surrounding mountainous areas - Yu Zhou; Guoping Li (Dynamics of Atmospheres and Oceans, 2024)

The impact of ammonifying microorganisms on the stabilization and carbon conversion of cow manure and wheat husk co-composting - Zhiming Xu; Ronghua Li; Jun Liu; Xuerui Xu; Shaowen Wang; Feng Gao; Guoping Yang; Yiqing Yao; Zengqiang Zhang; Xiu Zhang; Yong Zhang; Fusheng Quan (Chemical Engineering Journal, 2024)

Overexpression of VaBAM3 from Vitis amurensis enhances seedling cold tolerance by promoting soluble sugar accumulation and reactive oxygen scavenging - Guoping Liang; Han Wang; Huimin Gou; Min Li; Yongjuan Cheng; Baozhen Zeng; Juan Mao; Baihong Chen (Plant Cell Reports, 2024)

Residue levels, processing factors and risk assessment of pesticides in ginger from market to table - Kai Cui; Jian Wang; Guoping Ma; Shuai Guan; Jingyun Liang; Liping Fang; Ruiyan Ding; Teng Li; Zhan Dong; Xiaohu Wu; Yongquan Zheng (Journal of Hazardous Materials, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Highly efficient thermal decomposition of AP through intimately encapsulating in 3DOM CoFe2O4 spinel - Desheng Yang; Chaofei Bai; Fengdan Zhu; Chang Liu; Cheng Zhao Tu; Guoping Li; Yunjun Luo; Tianfu Zhang (Chemical Engineering Journal, 2024)

Effects of two strains of thermophilic nitrogen-fixing bacteria on nitrogen loss mitigation in cow dung compost - Shaowen Wang; Zhiming Xu; Xuerui Xu; Feng Gao; Kang Zhang; Xin Zhang; Xiu Zhang; Guoping Yang; Zengqiang Zhang; Ronghua Li; Fusheng Quan (Bioresource Technology, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Evaluation of annual production and economic benefits of tropical rice-crayfish coculture system in China - Yifan Li; Xucan Ku; Shaodong Wang; Guoping Pan; Qiyun Xu; Hongyan Liu; Jiaolong Li (Agricultural Systems, 2024)

Insight into the humification and carbon balance of biogas residual biochar amended co-composting of hog slurry and wheat straw - Yunpeng Liu; Junting Pan; Jingwen Wang; Xu Yang; Wanqiang Zhang; Kuok Ho Daniel Tang; Hailong Wang; Xiu Zhang; Runyu Gao; Guoping Yang; Zengqiang Zhang; Ronghua Li (Environmental Science and Pollution Research, 2024)

Dynamic hysteresis compensation and iterative learning control for underwater flexible structures actuated by macro fiber composites - Pengfei Zhan; Junqiang Lou; Tehuan Chen; Guoping Li; Chao Xu; Yanding Wei (Ocean Engineering, 2024)

CO2 capture using low silica X zeolite synthesized from low-grade coal gangue via a two-step activation method - Chenghao Liu; Fu Rao; Yalou Guo; Zhe Lu; Wenkang Deng; Guobiao Li; Hui Zhang; Tao Qi; Guoping Hu (Journal of Environmental Chemical Engineering, 2024)

Dynamic changes of zinc chemical speciation and zinc-containing peptides release in oysters (Crassostrea hongkongensis) during enzymatic hydrolysis - Ran Du; Wan Li; Jiawei Li; Shan Zeng; Zhongqin Chen; Jialong Gao; Huina Zheng; Haisheng Lin; Guoping Zhu; Xiaoming Qin; Wenhong Cao (Food Bioscience, 2024)

Establishing a pulmonary aspergillus fumigatus infection diagnostic platform based on RPA-CRISPR-Cas12a - Chunhui Lin; Jing Zhou; Nana Gao; Runde Liu; Ge Li; Jinyu Wang; Guoping Lu; Jilu Shen (World Journal of Microbiology and Biotechnology, 2024)

Estimation of evapotranspiration through an improved daily global solar radiation in SEBAL model: a case study of the middle Heihe River Basin - Jingqiu Yin; Xinfa Qiu; Shoubo Li; Guoping Shi; Huiyu Liu; Haixuan Zhou; Hanwei Wu (Theoretical and Applied Climatology, 2024)

Quantifying physiological contributions to yield loss in response to planting date in short-season cotton under a cotton wheat double-cropping system - Simeng Guo; Yingchun Han; Guoping Wang; Fengqi Wu; Yaoyu Jia; Jiale Chen; Xiaofei Li; Wenli Du; Yabing Li; Lu Feng (European Journal of Agronomy, 2024)

Dynamic Changes in Rhizosphere Microbial Communities of Watermelon During Continuous Monocropping with Gravel Mulch - Tingting Shen; Xiu Zhang; Li Li; Yuxi Qi; Hongfei Ji; Guoping Yang; Xue-Xian Zhang (Journal of Soil Science and Plant Nutrition, 2024)

Greenhouse cultivation enhances pesticide bioaccumulation in cowpeas following repeated spraying - Kai Cui; Jian Wang; Guoping Ma; Shuai Guan; Jingyun Liang; Liping Fang; Teng Li; Zhan Dong; Ruiyan Ding; Xiaohu Wu; Yongquan Zheng (Journal of Environmental Management, 2024)

Unique ternary Pd/NH2-MIL-125/CdIn2S4 composite expands the absorption range of visible light and improves H2 evolution efficiency - Man Zhang; Kangzheng Li; Zhe Yin; Zhichao Zhang; Qingcheng Luo; Binglin Tang; Guoping Yu; Tianding Hu; Shaoyun Shan (Journal of Environmental Chemical Engineering, 2024)

Biotic and abiotic effects of manganese salt and apple branch biochar co-application on humification in the co-composting of hog manure and sawdust - Xuan Wu; Xinyu Zhao; Weilong Wu; Jiawei Hou; Wanqiang Zhang; Daniel Kuok Ho Tang; Xiu Zhang; Guoping Yang; Zengqiang Zhang; Yiqing Yao; Ronghua Li (Chemical Engineering Journal, 2024)

Simultaneous decontamination of phosphorus and bisphenol A from livestock wastewater with boehmite-modified carbon composite - Yaru Peng; Xiu Zhang; Yuan Luo; Azeem Muhammad; Guoping Yang; Kuok Ho Daniel Tang; Zengqiang Zhang; Yuan Xu; Menghao Li; Jintong Cui; Ronghua Li (Bioresource Technology, 2024)

Geographic mosaics of rice domestication in the lower Yangtze River indicated by morphological characteristics of rice bulliform phytoliths - Keyang He; Yonglei Wang; Yunfei Zheng; Guoping Sun; Shao Lei; Yongning Li; Xiaoshan Yu; Jianping Zhang; Houyuan Lu (Archaeological and Anthropological Sciences, 2024)

Quantification and visualization of groundwater contamination prevention regionalization based on analytic hierarchy process method (AHP) in Guangdong-Hong Kong-Macao Greater Bay Area, South China - Zhou Cheng; Guoping Lu; Ming Wu; Zhaohui Li; Yirong Deng; Jinzhe Wu; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Journal of Hydrology, 2024)

Efficient self-cleaning and antibacterial ceramics with ultra-low doping and high exposure of silver - Kaibo Hu; Chuanqi Zhang; Guobiao Li; Yucheng Liu; Dong Wang; Ke Li; Guoping Hu; Liuyimei Yang; Yinhua Wan (Journal of Hazardous Materials, 2024)

HvBGlu3, a GH1 β-glucosidase enzyme gene, negatively influences β-glucan content in barley grains - La Geng; Mengdi Li; Shanggeng Xie; Han Wang; Xinyi He; Nannan Sun; Guoping Zhang; Lingzhen Ye (Theoretical and Applied Genetics, 2024)

Mechanism of Diabatic Heating on Precipitation and the Track of a Tibetan Plateau Vortex over the Eastern Slope of the Tibetan Plateau - Yuanchang Dong; Guoping Li; Xiaolin Xie; Long Yang; Peiwen Zhang; Bo Zeng (Advances in Atmospheric Sciences, 2024)

Mechanisms influencing changes in water cycle processes in the changing environment of the Songnen Plain, China - Zhong Lu; Kuo Li; Jinliang Zhang; Guoping Lei; Ziyang Yu; Chaoqun Li (Science of The Total Environment, 2023)

A strategy to prepare low-temperature curable photosensitive polyimide with good comprehensive performance - Shan Huang; Xialei Lv; Xingwang Lai; Jinhui Li; Yao Zhang; Siyao Qiu; Guoping Zhang; Rong Sun (Chemical Engineering Journal, 2023)

Prototypes, modifications, and hydrocarbon enrichment variations in basins influenced by Tethyan evolution: A comparative analysis of the Persian Gulf Basin and the Sichuan Basin - Zhiliang He; Zhijun Jin; Shuangjian Li; Guoping Bai; Xueyan Lv; Jinrui Guo; Jian Gao; Jinyin Yin; Yingqiang Li; Dingye Zheng (Science China Earth Sciences, 2023)

β-Sitosterol Alleviates Neuropathic Pain by Affect Microglia Polarization through Inhibiting TLR4/NF-κB Signaling Pathway - Yachun Zheng; Jiaji Zhao; Shiquan Chang; Zifeng Zhuang; Si Waimei; Xin Li; Zenni Chen; Bei Jing; Di Zhang; Guoping Zhao (Journal of Neuroimmune Pharmacology, 2023)

Synergistic leaching process for ion-exchange ammonium from weathered crust elution deposited rare earth tailings with potassium magnesium compound eluent - Xiaoju Li; Junxia Yu; Xiaodi Li; Guoping Song; Ze Ouyang; Rong Wang; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Environmental Science and Pollution Research, 2023)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

A Numerical Study of the Hydrodynamic Noise of Podded Propulsors Based on Proper Orthogonal Decomposition - Changsheng Chen; Guoping Li; Zhenlai Ma; Ziyi Mei; Bo Gao; Ning Zhang (Journal of Marine Science and Engineering, 2023)
Podded propulsors have become a focal point of research in the field of marine propulsion in recent years due to their high efficiency, low noise, and excellent maneuverability. To investigate the acoustic characteristics induced by the flow field of podded propulsors, a high-precision unsteady numerical simulation was conducted using the Delayed Detached Eddy Simulation (DDES) coupled with Ffowcs Williams–Hawkings (FW-H) equations. Multiple spatial acoustic receiving arrays were employed, and analysis methods including Proper Orthogonal Decomposition (POD) and Fast Fourier Transform (FFT) were utilized to determine the spatial distribution of the acoustic field of the podded propulsor. The results show that the blade passing frequency and the shaft frequency consistently dominate as the primary characteristic frequencies. On the plane of the propeller disk, the distribution of sound pressure levels is uniform without distinct directivity. Across the space curved surface, approximately the first ten POD modes encompass 99.8% of the total energy, and their spatial distribution characteristics of sound pressure are closely related to the pod structure. Additionally, these modes exhibit characteristic frequencies such as the blade passing frequency and shaft frequency. The spatial distribution of sound pressure at a single frequency on the spatial surface corresponds well with the results obtained from the POD analysis.

Quantification of two-site kinetic transport parameters of polystyrene nanoplastics in porous media - Yuheng Wu; Zhou Cheng; Ming Wu; Yanru Hao; Guoping Lu; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Chemosphere, 2023)

Dissolving self to protect community: cGAS ubiquitin-like mechanism for bacteria to fight against phages - Junyi Wang; Guoping Li; Min Wu (Science Bulletin, 2023)

Contrasting responses of spatiotemporal patterns of cropland to climate change in Northeast China - Ziyang Yu; Zhenzhen Li; Haoxuan Yang; Yihao Wang; Yang Cui; Guoping Lei; Shuai Ye (Food Security, 2023)

A global analysis on the relationship between water retention time and dissolved carbon across inland waters - Nan Jiang; Guoping Tang; Tao Chen; Xiangyu Niu; Yangbo Yu; Yi Li (Aquatic Sciences, 2023)

Growing cover crop mixtures are more sustainable than single cover crop in continuous cotton cropping: Comprehensive assessment from 3-year field experiment - Zhenggui Zhang; Jian Wang; Weibin Huang; Yingchun Han; Guoping Wang; Lu Feng; Xiaofei Li; Shiwu Xiong; Minghua Xin; Yabing Li; Zhanbiao Wang (Journal of Cleaner Production, 2023)

Dopamine/β-cyclodextrin synergistically modified core-shell MF@ZIF-8 porous membrane for high-efficient filtering of particulate matter (PM) in air and gathering oil in water - Zerong He; Nan Hu; Xiaoyun Meng; Jiang Li; Qi Wu; Guoping Yang; Wenyan Zhang; Yaoyu Wang (Chemical Engineering Journal, 2023)

Assessing Spatio-Temporal Variability of Soil Phosphorus in Different Cotton-Based Cropping Systems Using Geo-Statistics - Li Teng; Xiong Shiwu; Wang Zhanbao; Li Xiaofei; Han Yingchun; Wang Guoping; Lei Yaping; Feng Lu; Yang Beifang; Zhi Xiaoyu; Fan Zhengyi; Li Yabing (Journal of Soil Science and Plant Nutrition, 2023)

Monitoring of insecticide resistance for Apolygus lucorum populations in the apple orchard in China - Xueli Wang; Heng Su; Juan Wang; Guoping Li; Hongqiang Feng; Jinyong Zhang (Crop Protection, 2023)

Structure-guided camera localization for indoor environments - Qing Li; Rui Cao; Kanglin Liu; Zongze Li; Jiasong Zhu; Zhenyu Bao; Xu Fang; Qingquan Li; Xianfeng Huang; Guoping Qiu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Distinct resting-state functional connectivity patterns of Anterior Insula affected by smoking in mild cognitive impairment - Tianyi Zhang; Qingze Zeng; Kaicheng Li; Xiaocao Liu; Yanv Fu; Tiantian Qiu; Peiyu Huang; Xiao Luo; Zhirong Liu; Guoping Peng (Brain Imaging and Behavior, 2023)
Smoking is a modifiable risk factor for Alzheimer’s disease (AD). The insula plays a vital role in both smoking and cognition. However, the smoking effects on insula-related networks in cognitively normal controls (CN) and mild cognitive impairment (MCI) patients remain unknown. We identified 129 CN (85 non-smokers and 44 smokers) and 83 MCI (54 non-smokers and 29 smokers). Each underwent neuropsychological assessment and MRI (structural and resting-state functional). Seed-based functional analyses in the anterior and posterior insula were performed to calculate the functional connectivity (FC) with voxels in the whole brain. Mixed-effect analyses were performed to explore the interactive effects on smoking and cognitive status. Associations between FC and neuropsychological scales were assessed. Mixed-effect analyses revealed the FC differences between the right anterior insula (RAI) with the left middle temporal gyrus (LMTG) and that with the right inferior parietal lobule (RIPL) ( p < 0.01, cluster level < 0.05, two-tailed, gaussian random field correction). The FC of RAI in both LMTG and RIPL sees a significant decrease in MCI smokers ( p < 0.01). Smoking affects insula FC differently between MCI and CN, and could decrease the insula FC in MCI patients. Our study provides evidence of neural mechanisms between smoking and AD.

Correction to: Molecular characterization of a novel amalgavirus infecting lilium spp. in China - Zhihao Yuan; Zhenfeng Li; Yuexia Lu; Mengji Cao; Ni Hong; Guoping Wang; Li Cai (Archives of Virology, 2023)

Optimizing plant type structure to adjust the temporal and spatial distribution of water consumption and promote the growth and yield formation of cotton - Yaru Wang; Jiale Chen; Fengqi Wu; Beifang Yang; Yingchun Han; Lu Feng; Zhanbiao Wang; Xiaofei Li; Yaping Lei; Shiwu Xiong; Guoping Wang; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Molecular characterization of a novel amalgavirus infecting lilium spp. in China - Zhihao Yuan; Zhenfeng Li; Yuexia Lu; Mengji Cao; Ni Hong; Guoping Wang; Li Cai (Archives of Virology, 2023)

Evaluation on the rejuvenation and diffusion characteristics of waste cooking oil on aged SBS asphalt based on molecular dynamics method - Huanan Yu; Jinguo Ge; Guoping Qian; Chao Zhang; Wan Dai; Ping Li (Journal of Cleaner Production, 2023)

Important effects of polypropylene on migration of ciprofloxacin in groundwater - Yanna Chen; Cehui Mo; Ming Wu; Yanru Hao; Zhou Cheng; Guoping Lu; Qusheng Li; Bill X. Hu; Jianfeng Wu; Jichun Wu (Journal of Environmental Chemical Engineering, 2023)

Oxidative lipidomics to elucidate the non-volatile derivatives of four typical triglycerides in vegetable oils under simulated frying conditions - Qian Hu; Jiukai Zhang; Guoping Li; Liyang Wei; Chenchun Zhong; Ying Chen (Food Chemistry, 2023)

The Lnc-HOTAIR/miR122/PPARγ signaling mediated the occurrence and continuous development of alcohol-induced Osteonecrosis of the femoral head - Guoping Le; Mengting Lu; Li Li; Hanwen Luo (Toxicology Letters, 2023)

The nitrogen footprint and reactive nitrogen reduction potential of cotton production in China - Weibin Huang; Fengqi Wu; Zhenggui Zhang; Yongming Meng; Jian Wang; Qinqin Li; Yingchun Han; Lu Feng; Xiaofei Li; Guoping Wang; Yaping Lei; Zhengyi Fan; et al. (Journal of Cleaner Production, 2023)

Oocyte Arrested at Metaphase II Stage were Derived from Human Pluripotent Stem Cells in vitro - Xiaoli Yu; Ning Wang; Xiang Wang; Hehe Ren; Yanping Zhang; Yingxin Zhang; Yikai Qiu; Hongyan Wang; Guoping Wang; Xiuying Pei; Ping Chen; Yahui Ren; et al. (Stem Cell Reviews and Reports, 2023)
Initiation of meiosis is the most difficult aspect of inducing competent oocytes differentiation from human stem cells in vitro . Human induced pluripotent stem cells (hiPSCs) and embryonic stem cells (hESCs) were cultured with follicle fluid, cytokines and small molecule to induced oocyte-like cells (OLCs) formation through a three-step induction procedure. Expression of surface markers and differentiation potential of germ cells were analyzed in vitro by flow cytometry, gene expression, immunocytochemistry, western blotting and RNA Sequencing. To induce the differentiation of hiPSCs into OLCs, cells were firstly cultured with a primordial germ cell medium for 10 days. The cells exhibited similar morphological features to primordial germ cells (PGCs), high expressing of germ cell markers and primordial follicle development associated genes. The induced PGCs were then cultured with the primordial follicle-like cell medium for 5 days to form the induced follicle-like structures (iFLs), which retained both primordial oocytes-like cells and granulosa-like cells. In the third step, the detached iFLs were harvested and transferred to the OLC-medium for additional 10 days. The cultured cells developed cumulus-oocyte-complexes (COCs) structures and OLCs with different sizes (50–150 μm diameter) and a zona pellucida. The in vitro matured OLCs had polar bodies and were arrested at metaphase II (MII) stage. Some OLCs were self-activated and spontaneously developed into multiple-cell structures similar to preimplantation embryos, indicating that OLCs were parthenogenetically activated though in vitro fertilization potential of OLCs are yet to be proved. in vitro maturation of OLCs derived from hiPSCs provides a new means to study human germ cell formation and oogenesis. Graphical Abstract

Genomic insights into the genetic basis of cotton breeding in China - Yiqian Li; Zhanfeng Si; Guoping Wang; Zhuolin Shi; Jinwen Chen; Guoan Qi; Shangkun Jin; Zegang Han; Wenhao Gao; Yue Tian; Yun Mao; Lei Fang; et al. (Molecular Plant, 2023)

Pyridine N of N/Co-co-doped graphite gas diffusion electrode facilitating the efficient production of hydroxyl radicals in the electro-peroxone process - Qiang Bi; Sisi Jiang; Changfeng Hu; Li Zhang; Yilin Zhao; Bo Yang; Guoping Li; Juanqin Xue (Journal of Environmental Chemical Engineering, 2023)

Highly selective CO2 electrocatalytic reduction on nickel single-atom catalyst in a high-temperature shockwave method - Jiawei Wang; Guoping Xiao; Na Gao; Jing Zhou; Mengna Xie; XianLong Du; Chuanqiang Wu; Shibo Xi; Tao Li; Jian-Qiang Wang (Fuel, 2023)

Insight into boron-doped biochar as efficient metal-free catalyst for peroxymonosulfate activation: Important role of -O-B-O- moieties - Guoping Pan; Jia Wei; Mengdie Xu; Jiamei Li; Linhao Wang; Yanan Li; Nan Cui; Jun Li; Zhaoxu Wang (Journal of Hazardous Materials, 2023)

Climate warming accelerates cotton growth while cultivar shifts extend the growth period - Wanrui Han; Shengli Liu; Yaping Lei; Yongjiang Zhang; Yingchun Han; Guoping Wang; Lu Feng; Xiaofei Li; Yabing Li; Zhanbiao Wang (Field Crops Research, 2023)

Changes in within-boll yield components explain cotton yield and quality variation across planting dates under a double cropping system of cotton-wheat - Simeng Guo; Taijie Liu; Yingchun Han; Guoping Wang; Wenli Du; Fengqi Wu; Yabing Li; Lu Feng (Field Crops Research, 2023)

VaSUS2 confers cold tolerance in transgenic tomato and Arabidopsis by regulation of sucrose metabolism and ROS homeostasis - Yanmei Li; Guoping Liang; Guojie Nai; Shixiong Lu; Weifeng Ma; Zonghuan Ma; Juan Mao; Baihong Chen (Plant Cell Reports, 2023)

Orychophragmus violaceus/cotton relay intercropping with reduced N application maintains or improves crop productivity and soil carbon and nitrogen fractions - Zhenggui Zhang; Jian Wang; Shiwu Xiong; Weibin Huang; Xiaofei Li; Minghua Xin; Yingchun Han; Guoping Wang; Lu Feng; Yaping Lei; Beifang Yang; Yabing Li; et al. (Field Crops Research, 2023)

Quantitative evaluation of variation and driving factors of the regional water footprint for cotton production in China - Qinqin Li; Weibin Huang; Jian Wang; Zhenggui Zhang; Yabing Li; Yingchun Han; Lu Feng; Xiaofei Li; Beifang Yang; Guoping Wang; Yaping Lei; Shiwu Xiong; et al. (Sustainable Production and Consumption, 2023)

Ratiometric fluorescent sensing of phosphate ion in environmental water samples using flavin mononucleotide-functionalized Fe3O4 particles - Fang Xu; Wei Leng; Qinwei Lu; Kunpeng Li; Yukuai Zhang; Jingyu Liu; Liqiang Xu; Guoping Sheng (Science of The Total Environment, 2023)

Electron transfer mechanism mediated nitrogen-enriched biochar encapsulated cobalt nanoparticles catalyst as an effective persulfate activator for doxycycline removal - Zijian Jiang; Jia Wei; Yifei Zhang; Xiruo Niu; Jiamei Li; Yanan Li; Guoping Pan; Mengdie Xu; Xueru Cui; Nan Cui; Jun Li (Journal of Cleaner Production, 2023)

High-efficiency electro-Fenton process based on in-situ grown CoFeCe-LDH@CFs free-standing cathodes: Correlation of cerium and oxygen vacancies with H2O2 - Mengdie Xu; Jia Wei; Xueru Cui; Jiamei Li; Guoping Pan; Yanan Li; Zijian Jiang; Xiruo Niu; Nan Cui; Jun Li (Chemical Engineering Journal, 2023)

Near-ultraviolet emitters based on carbazole-imidazole for highly efficient solution-processed organic light-emitting diodes - Siyang Liu; Junzi Li; Huibo Yan; Fanghao Ye; Fangfang Niu; Bin Zhang; Guoping Wang; Guijun Li; Pengju Zeng (Chemical Engineering Journal, 2023)

Complexing agents-free bioelectrochemical trickling systems for highly-efficient mesothermal NO removal: The role of extracellular polymer substances - Xingzhu Huang; Shaofeng Zhou; Jianjun Li; Xiaojun Wang; Shaobin Huang; Guoping Sun; Shan Yang; Jia Xing; Meiying Xu (Bioresource Technology, 2023)

The AP2/ERF transcription factor SlERF.J2 functions in hypocotyl elongation and plant height in tomato - Yanan Chen; Hong Yang; Boyan Tang; Fenfen Li; Qiaoli Xie; Guoping Chen; Zongli Hu (Plant Cell Reports, 2022)

Identification and expression analysis of the grape pentatricopeptide repeat (PPR) gene family in abiotic stress - Lili Che; Shixiong Lu; Guoping Liang; Huimin Gou; Min Li; Baihong Chen; Juan Mao (Physiology and Molecular Biology of Plants, 2022)

The full-length genome sequence of a novel amalgavirus in Lilium spp. in China - Yanyan Huo; Xiaoting Li; Jiale Zhou; Shengjie Lin; Jiahao Ding; Huan Liu; Jianglian Yu; Ni Hong; Guoping Wang; Fang Ding (Archives of Virology, 2022)

Impact of Arctic Oscillation on cloud radiative forcing and September sea ice retreat - Yanxing Li; Liang Chang; Guoping Gao (Acta Oceanologica Sinica, 2022)

Molecular characterization of a new fusarivirus infecting Botryosphaeria dothidea, the causal agent of pear ring rot disease - Ying He; Qi Zou; Shanshan Li; Haodong Zhu; Ni Hong; Guoping Wang; Liping Wang (Archives of Virology, 2022)

Concentration and Distribution of Cu, Zn, Pb, and Cd in Mackerel Icefish (Champsocephalus gunnari) in South Georgia, Antarctic, During Winter - Guoping Zhu; Yingying Li; Danrong Wang; Hui Liu (Biological Trace Element Research, 2022)

Effect of maternal thallium exposure in early pregnancy on the risk of preterm birth - Xi Chen; Li Huang; Qian Li; Xu Zhang; Xiaoyi Wang; Guoqiang Sun; Nianhua Yi; Guoping Xiong; Xuefeng Yang; Liping Hao; Hongying Yang; Nianhong Yang (Environmental Science and Pollution Research, 2022)

An integrated analysis of single-cell and bulk transcriptomics reveals EFNA1 as a novel prognostic biomarker for cervical cancer - Xiaopeng Shen; Meng Li; Yang Lei; Shan Lu; Sufen Wang; Zhongxian Liu; Chunguang Wang; Yun Zhao; Ao Wang; Chao Bi; Guoping Zhu (Human Cell, 2022)

Changes in Typhoon Regional Heavy Precipitation Events over China from 1960 to 2018 - Yangmei Tian; John L. Mcbride; Fumin Ren; Guoping Li; Tian Feng (Advances in Atmospheric Sciences, 2022)
In earlier studies, objective techniques have been used to determine the contribution of tropical cyclones to precipitation (TCP) in a region, where the Tropical cyclone Precipitation Event (TPE) and the Regional Heavy Precipitation Events (RHPEs) are defined and investigated. In this study, TPE and RHPEs are combined to determine the Typhoon Regional Heavy Precipitation Events (TRHPEs), which is employed to evaluate the contribution of tropical cyclones to regional extreme precipitation events. Based on the Objective Identification Technique for Regional Extreme Events (OITREE) and the Objective Synoptic Analysis Technique (OSAT) to define TPE, temporal and spatial overlap indices are developed to identify the combined events as TRHPE. With daily precipitation data and TC best-track data over the western North Pacific from 1960 to 2018, 86 TRHPEs have been identified. TRHPEs contribute as much as 20% of the RHPEs, but 100% of events with extreme individual precipitation intensities. The major TRHPEs continued for approximately a week after tropical cyclone landfall, indicating a role of post landfall precipitation. The frequency and extreme intensity of TRHPEs display increasing trends, consistent with an observed positive trend in the mean intensity of TPEs as measured by the number of daily station precipitation observations exceeding 100 mm and 250 mm. More frequent landfalling Southeast and South China TCs induced more serious impacts in coastal areas in the Southeast and the South during 1990–2018 than 1960–89. The roles of cyclone translation speed and “shifts” in cyclone tracks are examined as possible explanations for the temporal trends.

Developmental Origins of Human Cortical Oligodendrocytes and Astrocytes - Lin Yang; Zhenmeiyu Li; Guoping Liu; Xiaosu Li; Zhengang Yang (Neuroscience Bulletin, 2022)
Human cortical radial glial cells are primary neural stem cells that give rise to cortical glutaminergic projection pyramidal neurons, glial cells (oligodendrocytes and astrocytes) and olfactory bulb GABAergic interneurons. One of prominent features of the human cortex is enriched with glial cells, but there are major gaps in understanding how these glial cells are generated. Herein, by integrating analysis of published human cortical single-cell RNA-Seq datasets with our immunohistochemistical analyses, we show that around gestational week 18, EGFR-expressing human cortical truncated radial glial cells (tRGs) give rise to basal multipotent intermediate progenitors (bMIPCs) that express EGFR, ASCL1, OLIG2 and OLIG1. These bMIPCs undergo several rounds of mitosis and generate cortical oligodendrocytes, astrocytes and olfactory bulb interneurons. We also characterized molecular features of the cortical tRG. Integration of our findings suggests a general picture of the lineage progression of cortical radial glial cells, a fundamental process of the developing human cerebral cortex.

Mdivi-1 Modulates Macrophage/Microglial Polarization in Mice with EAE via the Inhibition of the TLR2/4-GSK3β-NF-κB Inflammatory Signaling Axis - Xiaoqin Liu; Xiaojuan Zhang; Xiaojie Niu; Peijun Zhang; Qing Wang; Xiuhua Xue; Guobin Song; Jiezhong Yu; Guoping Xi; Lijuan Song; Yanhua Li; Cungen Ma (Molecular Neurobiology, 2022)

Identification and genomic characterization of a novel polymycovirus from Alternaria alternata causing watermelon leaf blight - Guoping Ma; Chunyan Wu; Yuting Li; Yiran Mi; Tao Zhou; Can Zhao; Xuehong Wu (Archives of Virology, 2022)

Longitudinal virological changes and underlying pathogenesis in hospitalized COVID-19 patients in Guangzhou, China - Zhengtu Li; Yinhu Li; Ruilin Sun; Shaoqiang Li; Lingdan Chen; Yangqing Zhan; Mingzhou Xie; Jiasheng Yang; Yanqun Wang; Airu Zhu; Guoping Gu; Le Yu; et al. (Science China Life Sciences, 2021)

Circulating microRNA-30a-5p, microRNA-101-3p, microRNA-140-3p and microRNA-141-3p as potential biomarkers for dexmedetomidine response in pediatric patients - Xinmei Cai; Bilian Li; Wei Wei; Yanping Guan; Xue Bai; Min Huang; Yaying Huang; Lili Rong; Xingrong Song; Guoping Zhong (European Journal of Clinical Pharmacology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

On the origin of SARS-CoV-2—The blind watchmaker argument - Chung-I Wu; Haijun Wen; Jian Lu; Xiao-dong Su; Alice C. Hughes; Weiwei Zhai; Chen Chen; Hua Chen; Mingkun Li; Shuhui Song; Zhaohui Qian; Qihui Wang; et al. (Science China Life Sciences, 2021)

Transcription Factor VAX1 Regulates the Regional Specification of the Subpallium Through Repressing Gsx2 - Yan Wen; Zihao Su; Ziwu Wang; Lin Yang; Guoping Liu; Zicong Shang; Yangyang Duan; Heng Du; Zhenmeiyu Li; Yan You; Xiaosu Li; Zhengang Yang; et al. (Molecular Neurobiology, 2021)

Homeobox Gene Six3 is Required for the Differentiation of D2-Type Medium Spiny Neurons - Xiaolei Song; Haotian Chen; Zicong Shang; Heng Du; Zhenmeiyu Li; Yan Wen; Guoping Liu; Dashi Qi; Yan You; Zhengang Yang; Zhuangzhi Zhang; Zhejun Xu (Neuroscience Bulletin, 2021)
Medium spiny neurons (MSNs) in the striatum, which can be divided into D1 and D2 MSNs, originate from the lateral ganglionic eminence (LGE). Previously, we reported that Six3 is a downstream target of Sp8/Sp9 in the transcriptional regulatory cascade of D2 MSN development and that conditionally knocking out Six3 leads to a severe loss of D2 MSNs. Here, we showed that Six3 mainly functions in D2 MSN precursor cells and gradually loses its function as D2 MSNs mature. Conditional deletion of Six3 had little effect on cell proliferation but blocked the differentiation of D2 MSN precursor cells. In addition, conditional overexpression of Six3 promoted the differentiation of precursor cells in the LGE. We measured an increase of apoptosis in the postnatal striatum of conditional Six3 -knockout mice. This suggests that, in the absence of Six3, abnormally differentiated D2 MSNs are eliminated by programmed cell death. These results further identify Six3 as an important regulatory element during D2 MSN differentiation.

Distinctive distributions of halophilic Archaea across hypersaline environments within the Qaidam Basin of China - Derui Zhu; Guoping Shen; Zhibo Wang; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Yongzhen Li; Rong Wang (Archives of Microbiology, 2021)

Characteristics and Causes of Extreme Rainfall Induced by Binary Tropical Cyclones over China - Mingyang Wang; Fumin Ren; Yanjun Xie; Guoping Li; Ming-Jen Yang; Tian Feng (Asia-Pacific Journal of Atmospheric Sciences, 2021)
Binary tropical cyclones (BTC) often bring disastrous rainfall to China. From the viewpoint of the extreme of the BTC maximum daily rainfall, the characteristics of BTC extreme rainfall (BTCER) during 1960–2018 are analyzed, using daily rainfall data; and some representative large-scale mean flows, in which the associated BTCs are embedded, are analyzed. Results show that the frequency of BTCER shows a decreasing trend [−0.49 (10 yr) −1 ] and is mainly distributed within the BTC heavy rainstorm interval (100 mm ≤ BTCER

Decoding Cortical Glial Cell Development - Xiaosu Li; Guoping Liu; Lin Yang; Zhenmeiyu Li; Zhuangzhi Zhang; Zhejun Xu; Yuqun Cai; Heng Du; Zihao Su; Ziwu Wang; Yangyang Duan; Haotian Chen; et al. (Neuroscience Bulletin, 2021)
Mouse cortical radial glial cells (RGCs) are primary neural stem cells that give rise to cortical oligodendrocytes, astrocytes, and olfactory bulb (OB) GABAergic interneurons in late embryogenesis. There are fundamental gaps in understanding how these diverse cell subtypes are generated. Here, by combining single-cell RNA-Seq with intersectional lineage analyses, we show that beginning at around E16.5, neocortical RGCs start to generate ASCL1 + EGFR + apical multipotent intermediate progenitors (MIPCs), which then differentiate into basal MIPCs that express ASCL1, EGFR, OLIG2, and MKI67. These basal MIPCs undergo several rounds of divisions to generate most of the cortical oligodendrocytes and astrocytes and a subpopulation of OB interneurons. Finally, single-cell ATAC-Seq supported our model for the genetic logic underlying the specification and differentiation of cortical glial cells and OB interneurons. Taken together, this work reveals the process of cortical radial glial cell lineage progression and the developmental origins of cortical astrocytes and oligodendrocytes.

Novel aqueous biphasic system based on ionic liquid for the simultaneous extraction of seven active pharmaceutical ingredients in aquatic environment - Weixia Li; Xiaomei Zheng; Guoping Tu; Suyin Zhang; Pengyue Zhang (Environmental Science and Pollution Research, 2021)

Big Data Nanoindentation and Analytics Reveal the Multi-Staged, Progressively-Homogenized, Depth-Dependent Upscaling of Rocks’ Properties - Shengmin Luo; Daeyoung Kim; Yongkang Wu; Yucheng Li; Dongfang Wang; Jinliang Song; Don J. DeGroot; Guoping Zhang (Rock Mechanics and Rock Engineering, 2021)

Inconsistent responses of soil microbial community structure and enzyme activity to nitrogen and phosphorus additions in two tropical forests - Suhui Ma; Guoping Chen; Wenguang Tang; Aijun Xing; Xiao Chen; Wen Xiao; Luhong Zhou; Jiangling Zhu; Yide Li; Biao Zhu; Jingyun Fang (Plant and Soil, 2021)

Dominant factor of dry‐wet change in China since 1960s - Jinqin Xu; Dandan Wang; Xinfa Qiu; Yan Zeng; Xiaochen Zhu; Mengxi Li; Yongjian He; Guoping Shi (International Journal of Climatology, 2021)
The dry‐wet climate conditions of an area are mainly determined by the water input (e.g., precipitation, P) and output (e.g., potential evapotranspiration, PET). Based on three dry‐wet indices and the differential equation, this study designed a new attribution method to quantify the contributions of P and PET to the dry‐wet change, so as to determine the dominant factors of the dry‐wet change over whole China (CHINA) and various hydroclimate regions (i.e., arid region, AR; semi‐arid region, SAR; semi‐humid region, SHR; and humid region, HR) during 1960–2018 and six interdecadal periods. Results showed that the overall weak drying in CHINA was dominated by an increase in PET, while climate humidification in AR and HR was dominated by an increase in P, climate drying in SHR was dominated by the reduced P, and the weak drying in SAR was co‐dominated by P and PET during 1960–2018. The dominant factors of dry‐wet change over CHINA and each hydroclimate region varied in different decades. Briefly, climate humidification in CHINA and various hydroclimate regions was basically dominated by P in different decades, and the drying was mainly dominated by P in the 1960s–1980s, but the contribution of PET to climate drying began to become prominent after the 1980s. Besides, we found that P contributed more to dry‐wet change than PET on the station and regional scales, but the contribution of P to climate drying on a national scale was underestimated to some extent due to the regional offset effect of the increase/decrease in P during 1960–2018, as well as in the 1990s. These findings implied that the importance of research on the regional or local scale, and equal attention should be paid to the effects of P and PET changes in the future drought or dry‐wet change research.

Genetic and clinical determinants of mizoribine pharmacokinetics in renal transplant recipients - Rui Dai; Jingjie Li; Jingjing Wu; Qian Fu; Jiajia Yan; Guoping Zhong; Changxi Wang; Xiao Chen; Pan Chen (European Journal of Clinical Pharmacology, 2021)

The influence on carbon, nitrogen recycling, and greenhouse gas emissions under different C/N ratios by black soldier fly - Wancheng Pang; Dejia Hou; Elhosseny E. Nowar; Huanchun Chen; Jibin Zhang; Guoping Zhang; Qing Li; Shucai Wang (Environmental Science and Pollution Research, 2020)

Study of the geostatistical grid maths operation method of quantifying water movement in soil layers of a cotton field * - Liyuan Liu; Fangfang Xing; Yabing Li; Yingchun Han; Zhanbiao Wang; Xiaoyu Zhi; Guoping Wang; Lu Feng; Beifang Yang; Yaping Lei; Zhengyi Fan; Wenli Du (Irrigation and Drainage, 2020)
The precise quantification of water movement in different field soil layers is important for variable‐rate irrigation and fertilization. To this end, a field experiment based on a geostatistical approach was conducted in southern Anyang, Henan, China, to examine soil water movement in a cotton field with drip irrigation by measuring the soil water content (SWC) data on a regular 100 × 80 cm grid. The result shows that the temporal and spatial variation of soil moisture decreased with the increase of soil depth at different points, and apparent spatial heterogeneity was observed under different soil conditions through a semivariogram analysis. The variation of soil moisture at different soil profiles was affected by the cotton plants and drip lines in non‐irrigation and irrigation periods respectively. The level of the change at 20 cm was more than 70 cm in the horizontal direction in the two periods, however the degree of change at 40 cm in the irrigation period was more than 70 cm in the vertical direction, while contrary results were shown in the non‐irrigation period. Moreover, the results indicated that the trapezoidal rule could be applied to quantify the volume of water movement precisely.

Establishment of an Objective Standard for the Definition of Binary Tropical Cyclones in the Western North Pacific - Fumin Ren; Yanjun Xie; Biwen Yin; Mingyang Wang; Guoping Li (Advances in Atmospheric Sciences, 2020)

An evaluation of the core bacterial communities associated with hypersaline environments in the Qaidam Basin, China - Derui Zhu; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Yongzhen Li; Rong Wang (Archives of Microbiology, 2020)

Do the performance and efficiency of China’s carbon emission trading market change over time? - Shiyi Zhang; Kai Jiang; Lan Wang; Geoff Bongers; Guoping Hu; Jia Li (Environmental Science and Pollution Research, 2020)

Sideswiping Tropical Cyclones and Their Associated Precipitation over China - Tian Feng; Fumin Ren; Da-Lin Zhang; Guoping Li; Wenyu Qiu; Hui Yang (Advances in Atmospheric Sciences, 2020)

Silencing of the MADS-Box Gene SlMADS83 Enhances Adventitious Root Formation in Tomato Plants - Anzhou Li; Guoping Chen; Yunshu Wang; Honglian Liang; Zongli Hu (Journal of Plant Growth Regulation, 2020)

Cardiac-specific LRP6 knockout induces lipid accumulation through Drp1/CPT1b pathway in adult mice - Ying Wang; Chao Yin; Zhidan Chen; Yang Li; Yan Zou; Xiang Wang; Yanpeng An; Feizhen Wu; Guoping Zhang; Chunjie Yang; Huiru Tang; Yunzeng Zou; et al. (Cell and Tissue Research, 2020)

Antimony removal from wastewater by sulfate-reducing bacteria in a bench-scale upflow anaerobic packed-bed reactor - Jingjing Chen; Guoping Zhang; Chao Ma; Dongli Li (Acta Geochimica, 2020)

Characterization of Shale Softening by Large Volume-Based Nanoindentation - Yunhu Lu; Yucheng Li; Yongkang Wu; Shengmin Luo; Yan Jin; Guoping Zhang (Rock Mechanics and Rock Engineering, 2020)

Enhancing remote sensing image retrieval using a triplet deep metric learning network - Rui Cao; Qian Zhang; Jiasong Zhu; Qing Li; Qingquan Li; Bozhi Liu; Guoping Qiu (International Journal of Remote Sensing, 2020)

Improving the attractiveness and accessibility of campus green space for developing a sustainable university environment - Xinqin Li; Guoping Ni; Bart Dewancker (Environmental Science and Pollution Research, 2019)

Microbes: the hidden giant behind the biogeochemical cycling of elements in the hydrosphere - Li Huang; Xiang Xiao; Guoping Zhao (Science China Life Sciences, 2019)

The bHLH transcription factor SlPRE2 regulates tomato fruit development and modulates plant response to gibberellin - Zhiguo Zhu; Honglian Liang; Guoping Chen; Fenfen Li; Yunshu Wang; Changguang Liao; Zongli Hu (Plant Cell Reports, 2019)

The tomato MADS-box gene SlMBP9 negatively regulates lateral root formation and apical dominance by reducing auxin biosynthesis and transport - Anzhou Li; Guoping Chen; Xiaohui Yu; Zhiguo Zhu; Lincheng Zhang; Shengen Zhou; Zongli Hu (Plant Cell Reports, 2019)

Lasting days contributed most to the variation of ≥ 10 °C accumulated temperature from 1961 to 2010 in China - Jinqin Xu; Xinfa Qiu; Yan Zeng; Mengxi Li; Guoping Shi; Zhe Wang; Xiaochen Zhu; Dandan Wang (Theoretical and Applied Climatology, 2019)

Determination of the embedded length of stabilizing piles in colluvial landslides with upper hard and lower weak bedrock based on the deformation control principle - Changdong Li; Junfeng Yan; Junjie Wu; Guoping Lei; Liangqing Wang; Yongquan Zhang (Bulletin of Engineering Geology and the Environment, 2019)

N-(3-oxo-acyl) homoserine lactone induced germ cell apoptosis and suppressed the over-activated RAS/MAPK tumorigenesis via mitochondrial-dependent ROS in C. elegans - Bin Chen; Xianbin Cao; Huayi Lu; Pengbo Wen; Xiaojing Qi; Shaopeng Chen; Lijun Wu; Chi Li; An Xu; Guoping Zhao (Apoptosis, 2018)

Determining the Effect of pH on the Partitioning of Neutral, Cationic and Anionic Chemicals to Artificial Sebum: New Physicochemical Insight and QSPR Model - Senpei Yang; Lingyi Li; Tao Chen; Lujia Han; Guoping Lian (Pharmaceutical Research, 2018)

A histone deacetylase gene, SlHDA3, acts as a negative regulator of fruit ripening and carotenoid accumulation - Jun-E Guo; Zongli Hu; Xiaohui Yu; Anzhou Li; Fenfen Li; Yunshu Wang; Shibing Tian; Guoping Chen (Plant Cell Reports, 2018)

ZIKA virus isolated from mosquitoes: a field and laboratory investigation in China, 2016 - Shihong Fu; Song Song; Hong Liu; Yuanyuan Li; Xiaolong Li; Xiaoyan Gao; Ziqian Xu; Guoping Liu; Dingming Wang; Zhenzao Tian; Jingzhu Zhou; Ying He; et al. (Science China Life Sciences, 2017)

Forced hot-air treatment against Bactrocera papayae (Diptera: Tephritidae) in papaya - Bo Liu; Baishu Li; Guoping Zhan; Tao Zha; Yuejin Wang; Chen Ma (Applied Entomology and Zoology, 2017)

Modification of the SUNFLUX solar radiation scheme with a new aerosol parameterization and its validation using observation network data - Yongjian He; Zhi’an Sun; Guoping Shi; Jingmiao Liu; Jiandong Li (Advances in Atmospheric Sciences, 2017)

Physiological characterizations of three barley genotypes in response to low potassium stress - Zhilan Ye; Jianbin Zeng; Xing Li; Fanrong Zeng; Guoping Zhang (Acta Physiologiae Plantarum, 2017)

Fourth Industrial Revolution: technological drivers, impacts and coping methods - Guoping Li; Yun Hou; Aizhi Wu (Chinese Geographical Science, 2017)

Fluid inclusions and C-H-O-S isotope systematics of early Permian porphyry Mo mineralization of the West Junggar region, NW China: the Suyunhe example - Chong Cao; Ping Shen; Changhao Li; Guoping Zheng (International Geology Review, 2017)

Bisphenol A Represses Dopaminergic Neuron Differentiation from Human Embryonic Stem Cells through Downregulating the Expression of Insulin-like Growth Factor 1 - Boxian Huang; Song Ning; Qinjing Zhang; Aiqin Chen; Chunyan Jiang; Yugui Cui; Jian Hu; Hong Li; Guoping Fan; Lianju Qin; Jiayin Liu (Molecular Neurobiology, 2017)

Analysis of the mechanism underlying Tibetan Plateau vortex frequency difference between strong and weak MJO periods - Guoping Li; Fuhu Zhao (Journal of Meteorological Research, 2017)

Analysis of a vortex precipitation event over Southwest China using AIRS and in situ measurements - Chengcheng Ni; Guoping Li; Xiaozhen Xiong (Advances in Atmospheric Sciences, 2017)

Regional study on investment for transmission infrastructure in China based on the State Grid data - Wendong Wei; Xudong Wu; Xiaofang Wu; Qiangmin Xi; Xi Ji; Guoping Li (Frontiers of Earth Science, 2017)

Climatology of monsoon precipitation over the Tibetan Plateau from 13-year TRMM observations - Bai Aijuan; Li Guoping (Theoretical and Applied Climatology, 2016)

Influence of reducing conditions on the release of antimony and arsenic from a tailings sediment - Zhiping Fu; Guoping Zhang; Haixia Li; Jingjing Chen; Fengjuan Liu; Qiong Wu (Journal of Soils and Sediments, 2016)

Statistical characteristics and formation mechanism of the Lanyu cold eddy - Ruili Sun; Yanzhen Gu; Peiliang Li; Lei Li; Fangguo Zhai; Guoping Gao (Journal of Oceanography, 2016)

Identification of a divergent variant of grapevine berry inner necrosis virus in grapevines showing chlorotic mottling and ring spot symptoms - Xudong Fan; Ni Hong; Zunping Zhang; Zuokun Yang; Fang Ren; Guojun Hu; Zhengnan Li; Jun Zhou; Yafeng Dong; Guoping Wang (Archives of Virology, 2016)

LincRNA1230 inhibits the differentiation of mouse ES cells towards neural progenitors - Chenxin Wang; Guoping Li; Yukang Wu; Jiajie Xi; Jiuhong Kang (Science China Life Sciences, 2016)

Development of a sensitive molecular detection assay for mango malformation disease caused by Fusarium mangiferae - Jingbo Wu; Feng Liu; Rulin Zhan; Guoping Li; Yanlong Zhao; Chang Jinmei; Yanbiao He (Biotechnology Letters, 2016)

Distribution characteristics and source apportionment of polycyclic aromatic hydrocarbons (PAHs) in the Liao River drainage basin, northeast China - Jian Hu; Congqiang Liu; Guoping Zhang; Yanlin Zhang; Siliang Li; Zhiqi Zhao; Baojian Liu; Qinjun Guo (Environmental Monitoring and Assessment, 2016)

Why the spring North Pacific Oscillation is a predictor of typhoon activity over the Western North Pacific - Dong Chen; Huijun Wang; Jiping Liu; Guoping Li (International Journal of Climatology, 2015)
In this study, we investigated the impact of the spring North Pacific Oscillation ( NPO ) on typhoon frequency over the Western North Pacific ( WNP , north of the equator and west of dateline). To reduce the statistical uncertainty, all the data we used have been excluded the El Nino/Southern Oscillation signals. We found that the spring NPO positively correlated with the annual typhoon number over the WNP (hereafter TNWNP ) during the period 1968–2010, with a correlation coefficient of 0.62 (above the 99% significance level). When the Northern Low and Southern High pattern over the north Pacific weakens, the TNWNP tends to increase. A positive phase of spring NPO is associated with the tropical circulation and sea surface temperature ( SST ) anomalies in the North Pacific, which may lead to unfavorable dynamical and thermal conditions for typhoon genesis over the WNP during JJAS . The negative anomaly of SST over the WNP , associated with the positive spring NPO anomaly, is connected to the tropical atmospheric circulations from spring to summer via good oceanic seasonal persistence and air–sea interaction. Thus, the spring NPO ‐related variability of the tropical atmospheric circulation as well as the SST can affect typhoon activity over the WNP . In addition, the spring NPO can also be adopted as a predictor for the summer rainfall in South China, since the spring NPO can modulate the WNP SST and western Pacific subtropical high from spring to summer.

Assessment of the Altitudinal Atmospheric Metal(loid) Deposition in a Mountainous City by Mosses - Haixia Li; Guoping Zhang; Hong Liu; Ling Li; Zhiping Fu; Xiaoxue Ouyang; Jingjing Chen; Jian Hu (Bulletin of Environmental Contamination and Toxicology, 2015)

QTL analysis of three flower-related traits based on an interspecific genetic map of Luffa - Junjie Cui; Jiaowen Cheng; Guoping Wang; Xin Tang; Zhiming Wu; Mingbao Lin; Lianfang Li; Kailin Hu (Euphytica, 2015)

Heterologous Expression of BoPAP1 in Tomato Induces Stamen Specific Anthocyanin Accumulation and Enhances Tolerance to a Long-Term Low Temperature Stress - Lijun Ren; Zongli Hu; Yali Li; Bin Zhang; Yanjie Zhang; Yun Tu; Guoping Chen (Journal of Plant Growth Regulation, 2014)

Effects of industrial relocation on Chinese regional economic growth disparities: Based on system dynamics modeling - Aizhi Wu; Guoping Li; Tieshan Sun; Yusheng Liang (Chinese Geographical Science, 2014)

Optimization of well placement by combination of a modified particle swarm optimization algorithm and quality map method - Shuaiwei Ding; Hanqiao Jiang; Junjian Li; Guoping Tang (Computational Geosciences, 2014)

Impact of regional development on carbon emission: Empirical evidence across countries - Guoping Li; Yuan Yuan (Chinese Geographical Science, 2014)

Heavy metals and polycyclic aromatic hydrocarbons in sediments from the Shenzhen River, South China - Guoping Deng; Wenqing Yang; Guanye Zhou; Yun Li; Shili Liu (Environmental Science and Pollution Research, 2014)

Bombyx mori Nucleopolyhedrovirus ORF101 Encodes a Budded Virus Envelope Associated Protein - Huiqing Chen; Mei Li; Guoping Huang; Weijun Mai; Keping Chen; Yajing Zhou (Current Microbiology, 2014)

Codon Optimization Enhances Protein Expression of Bombyx mori Nucleopolyhedrovirus DNA Polymerase in E. coli - Huifang Song; Guohui Li; Weijun Mai; Guoping Huang; Keping Chen; Yajing Zhou; Huiqing Chen (Current Microbiology, 2014)

Dynamic and numerical study of waves in the Tibetan Plateau Vortex - Gong Chen; Guoping Li (Advances in Atmospheric Sciences, 2014)

Cloning and characterization of a novel apolipoprotein gene, apolipoprotein AV, in tree shrews - Guoping Li; Huairong Luo; Guotao Sun; Guisheng Wu; Gang Wu; Yan Wang; Yong Man; Shu Wang; Jian Li; Baosheng Chen (Molecular Biology Reports, 2013)

Suburbanization and subcentering of population in Beijing metropolitan area: A nonparametric analysis - Tieshan Sun; Zhenhai Han; Lanlan Wang; Guoping Li (Chinese Geographical Science, 2012)

A putative functional MYB transcription factor induced by low temperature regulates anthocyanin biosynthesis in purple kale (Brassica Oleracea var. acephala f. tricolor) - Bin Zhang; Zongli Hu; Yanjie Zhang; Yali Li; Shuang Zhou; Guoping Chen (Plant Cell Reports, 2012)

Performance of a biotrickling filter in the removal of waste gases containing low concentrations of mixed VOCs from a paint and coating plant - Jianjun Li; Guangyun Ye; Duanfang Sun; Taicheng An; Guoping Sun; Shizhong Liang (Biodegradation, 2012)

Simvastatin augments the efficacy of therapeutic angiogenesis induced by bone marrow-derived mesenchymal stem cells in a murine model of hindlimb ischemia - Yuqing Zhang; Rusheng Zhang; Yong Li; Guoping He; Dingguo Zhang; Fumin Zhang (Molecular Biology Reports, 2012)

Empirical study on effect of industrial structure change on regional economic growth of Beijing-Tianjin-Hebei Metropolitan Region - Hongxia Chen; Guoping Li (Chinese Geographical Science, 2011)

Association between the IL7R T244I polymorphism and multiple sclerosis: a meta-analysis - Ruijie Zhang; Lian Duan; Yongshuai Jiang; Xuehong Zhang; Peng Sun; Jin Li; Mingming Zhang; Guoping Tang; Xing Wang; Xia Li (Molecular Biology Reports, 2011)

Effect of ac68 Knockout and lef3 Leading Sequence Disruption on Viral Propagation - Guohui Li; Huiqing Chen; Qi Tang; Guoping Huang; Riqiang Deng; Jinwen Wang; Xunzhang Wang (Current Microbiology, 2011)

Development of environmental monitoring satellite systems in China - GuoPing Li; ChunXiang Cao (Science China Earth Sciences, 2010)

Paleosalinity in the Tianluoshan site and the correlation between the Hemudu culture and its environmental background - Minglin Li; Duowen Mo; Longjiang Mao; Guoping Sun; Kunshu Zhou (Journal of Geographical Sciences, 2010)

Characterization of Bombyx mori parvo-like virus non-structural protein NS1 - Guohui Li; Chen Sun; Junhong Zhang; Yuanqing He; Huiqing Chen; Jie Kong; Guoping Huang; Keping Chen; Qin Yao (Virus Genes, 2009)

Heterologous synthesis and assembly of functional LHII antenna complexes from Rhodovulum sulfidophilum in Rhodobacter sphaeroides mutant - Wanneng Wang; Zongli Hu; Xuqing Chen; Zhiping Zhao; Jinzhe Li; Guoping Chen (Molecular Biology Reports, 2009)

Identification of QTLs associated with salinity tolerance at late growth stage in barley - Dawei Xue; Youzong Huang; Xiaoqi Zhang; Kang Wei; Sharon Westcott; Chengdao Li; Mingcan Chen; Guoping Zhang; Reg Lance (Euphytica, 2009)

Centrifugal forces within usually-used magnitude elicited a transitory and reversible change in proliferation and gene expression of osteoblastic cells UMR-106 - Juan Li; Lingyong Jiang; Ga Liao; Guoping Chen; Ying Liu; Jun Wang; Yi Zheng; Songjiao Luo; Zhihe Zhao (Molecular Biology Reports, 2009)

Sodium butyrate-induced upregulation of p18 INK4C gene affects K562 cell G0/G1 arrest and differentiation - Lin Li; Guoping Zhang; Ye Zhang; Jiang Tan; Hui Huang; Baiqu Huang; Jun Lu (Molecular and Cellular Biochemistry, 2008)

The role of extracellular matrix, integrins, and cytoskeleton in mechanotransduction of centrifugal loading - Juan Li; Zhihe Zhao; Jun Wang; Guoping Chen; Jingyuan Yang; Songjiao Luo (Molecular and Cellular Biochemistry, 2008)

Osteoblast cytoskeletal modulation in response to compressive stress at physiological levels - Juan Li; Guoping Chen; Leilei Zheng; Songjiao Luo; Zhihe Zhao (Molecular and Cellular Biochemistry, 2007)

Identification and characterization of odv-e25 of Spodoptera litura multicapsid nucleopolyhedrovirus - Zhaofei Li; Lijin Pan; Hang Yu; Sainan Li; Guoping Zhang; Yi Pang (Virus Genes, 2006)

The Elp3 subunit of human Elongator complex is functionally similar to its counterpart in yeast - Fen Li; Jun Lu; Qiuju Han; Guoping Zhang; Baiqu Huang (Molecular Genetics and Genomics, 2005)

Site-Specific Integration of the Double-Mutation Glucose Isomerase (GIG138PG247D) Gene in Streptomyces lividans and Its Stable Expression - Yonghui Yang; Chong Xu; Feng Ge; Zhiqiang Lu; Guoping Zhu; Hui Li; Jun Liao; Liwen Niu; Yuzhen Wang; Mian Wu (Current Microbiology, 2002)

The effects of anomalous snow cover of the Tibetan Plateau on the surface heating - Li Guoping; Lu Jinghua; Jin Bingling; Bu Nima (Advances in Atmospheric Sciences, 2001)

Heterologous Expression of the Single-Mutation Glucose Isomerase (GIG138P) Gene in Streptomyces lividans and Its Genetic Instability - Yonghui Yang; Chong Xu; Feng Ge; Zhiqiang Lu; Guoping Zhu; Hui Li; Jun Liao; Maikun Teng; Liwen Niu; Yuzhen Wang (Current Microbiology, 2001)

Some important characteristics of surface albedo of China in recent years - Guoping Li; Zhonglin Chen (Chinese Geographical Science, 1997)

Determination of the Drag Coefficient over the Tibetan Plateau - Li Guoping; Duan Tingyang; Wan Jun; Gong Yuanfa; Shigenori Haginoya; Chen Longxun; Li Weiliang (Advances in Atmospheric Sciences, 1996)

Some possible solutions of nonlinear internal inertial gravity wave equations in the atmosphere - Li Guoping; Lu Jinghua (Advances in Atmospheric Sciences, 1996)